Pamekasan’s Traditional Dance Exploration as A Learning Source for Elementary School Students - Perdana, Parrisca Indra; Harsiwi, Nova Estu (Widyagogik, 2024)
The Getak Mask Dance (topeng dance) and the Rondhing Dance are emblematic forms of expression that originated and raised in Pamekasan. In the year of 2023, the Getak Mask (topeng) Dance was bestowed with the esteemed title of being recognized as a National Intangible Cultural Heritage site. Diligent endeavors persist to safeguard the heritage of this distinct dance. Among the measures undertaken to nurture its preservation, an emphasis has been placed on integrating this remarkable dance into the educational activities of elementary school students. The prime objective of this study is to delve into the rich repertoire of Pamekasan's distinctive dances, which can be effectively incorporated as educational resources for elementary school students. In this exploration, a combination of interview techniques, astute observations, and comprehensive document analysis have been employed. The data collected has been analyzed in a descriptive and qualitative manner. The findings of this research underscore that the aforementioned dance can indeed be utilized as an educational resource, shedding light on its historical genesis, progressive development, diverse movements, as well as its intricate makeup and fashion. Contrarily, the Rondhing Dance exhibits a simplicity and repetitive nature, aligning perfectly with the inherent characteristics of elementary school students' movements. Consequently, it enables the students to wholeheartedly engage in the dance, resonating with its distinct nuances. Conversely, due to its elevated level of technical proficiency and appreciation, the Getak Mask Dance renders it less accessible for elementary school students to perform with utmost appreciation.